Optimizing Natural Resource Value-Added through Creative Human Capital Empowerment in the Regional Digital Economy Ecosystem - Syamsu Rijal; Muhammad Nur Afiat; Mustari; Marhawati Najib (Citakonsultindo, 2026)
The world economy is changing, and this research examines how to maximize profits from a place's natural resources. It does this by building the skills of inventive people in the area’s digital world. Essentially, it’s about how combining digital tools with people’s imagination can turn basic materials into things that are actually in demand and worth a lot of money. After a thorough review of past research, the report shows that a combination of government plans to process materials using digital means and increasing the skills of the people who live in the area is the most important way to establish growth for the region that’s both lasting and benefits everyone. The creative economy isn't just something to help the economy; it’s the main thing that will allow a region to rely less on selling off raw materials and more on new ideas. The findings offer guidance to those in charge of areas, showing them how to build an economic development plan that considers future resource management and strengthens the digital market.